Factors influencing retention of engineers in South African coal power stations. - Myeza, Angela (My University, 2014)
ABSTRACT There is a looming shortage of skilled employees that possess high performance qualities. Moreover, the skills possessed by knowledge workers are sought after. However, research shows that the pool from which organisations pick these workers is shrinking. Organisations that fail to retain high performers may be left with the low performers, which negatively affects their competitive advantage and it has been shown that when an employee leaves an organisation, the profitability of the company is affected in a negative way too. Power stations are not immune and find themselves facing the very same challenge when it comes to retaining their engineers. Given this predicament in which organisations find themselves, this research identifies the factors that influence engineers to stay in employment at coal power stations and determines how these factors are ranked in order of relative importance. A survey was conducted at the power stations using a self-completion questionnaire, which the engineers were requested to complete to determine factors contributing to their retention. It was found that the most important factor to the engineers was the availability of career advancement opportunities. Organisational culture was found to be unimportant when compared to the other factors. Given the relatively young work force at the stations, it makes sense that career advancement is the priority. Engineers want to see their careers progress and want a clear path to be drawn showing the direction and possible speed at which they can advance to the next level. The young engineer is flexible and does not hesitate to take the next best available opportunity and knows that he is in demand for his skills and power stations need to realise that to retain this breed of engineers, they need to put effort into assisting the engineers to progress in their career aspirations.
MBA 2014
Keywords: Employee retention, Engineers -- Employment .